Analysis of Profitability, Dividend Policy, Sales Growth, Firm Size and Firm Value of Food and Beverage Companies on the IDX - Muhamad Al Ikhsan; Solikah Nurwati; Rita Sarlawa (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Purpose – This study was conducted to analyze the effect of profitability, dividendpolicy, and sales growth on firm value with firm size as a moderating variable.Design/Methodology/Approach – The research method used is descriptivequantitative. This study uses secondary data on the financial statements of food andbeverage companies listed on the Indonesia Stock Exchange in 2017-2020. Thesamples used was 9 companies and sample selection used purposive samplingtechnique. In this study using PLS analysis tool with WarpPLS 8.0 software.Findings - The results of this study indicate that profitability has a positivesignificant effect on firm value, dividend policy is not significant on firm value, salesgrowth has a positive significant on firm value, firm size has a positive significant effect on firm value. Firm size weakens and is not significant in moderating the effectof profitability on firm value, firm size strengthens and is not significant inmoderating the effect of dividend policy and sales growth on firm value.